Urban soil and agroecology as pillars for the metropolis of the future: Socio-environmental challenges and perspectives for sustainable cities - Assis, Lucas Lenin Resende de (National Journal of City Management, 2026)
Objective – To analyze the territory of Bahia from the perspective of urban soil, an element often overlooked in urban planning, arguing that understanding it as a living territory is strategic for sustainability and environmental justice. Methodology – An interdisciplinary theoretical study combining geography, soil science, and agroecology, structured around three axes: urban socio-environmental challenges, socio-spatial vulnerabilities of neoliberal urbanization, and design perspectives for resilience and sustainable urban planning. Originality/relevance – The work fills a theoretical gap by highlighting urban soil as a central object of analysis in the context of the climate crisis and urban planning. Its academic relevance lies in proposing an interdisciplinary agenda that combines sustainability, resilience, and environmental justice. Results – It is evident that excessive waterproofing, irregular occupation of slopes, and degradation of green areas increase flooding, landslides, and heat islands, reinforcing social and environmental vulnerabilities. The study also identifies urban planning practices that can strengthen socio-environmental resilience. Theoretical/methodological contributions – Integrates concepts of soil, urbanism, and agroecology, providing an analytical basis for future studies on sustainable cities. Social and environmental contributions – Highlights the importance of valuing soil and agroecology as pillars for more inclusive, sustainable, and environmentally just metropolises, promoting strategies that reduce socio-environmental risks and strengthen the right to the city.